Lung cancer trends and tumor characteristic changes over 20 years (2000-2020): Results of three French consecutive nationwide prospective cohorts' studies - Didier Debieuvre; Olivier Molinier; Lionel Falchero; Chrystèle Locher; Dorine Templement-Grangerat; Nicolas Meyer; Hugues Morel; Yannick Duval; Bernard Asselain; Alexia Letierce; Jean Trédaniel; Jean-Bernard Auliac; et al. (Elsevier, 2022)
Summary: Background: Long-term changes in lung cancer (LC) patients are difficult to evaluate. We report results from the French KBP-2020 real-life cohort. Methods: KBP-2020 was a prospective cohort that included all patients diagnosed with LC in 2020, in nonacademic public hospital in France. Patient and tumour characteristics were described and compared with similarly designed cohorts in 2000 and 2010. Findings: In 2020, 82 centers included 8,999 patients diagnosed with LC. The proportion of women increased: 34·6% (3114/8999) compared to, 24·3% (1711/7051) and 16·0% (904/5667) in 2010 and 2000 (p<0·0001). The proportion of non-smokers was higher in 2020 (12·6%, 1129/8983) than in previous cohorts (10·9% (762/7008) in 2010; 7·2% (402/5586) in 2000, p<0·0001). In 2020, at diagnosis, 57·6% (4405/7648) of patients had a metastatic/disseminated stage non-small-cell lung cancer (NSCLC) (58·3% (3522/6046) in 2010; 42·6% (1879/4411) in 2000, p<0·0001). Compared with 2000 and 2010 data, early survival improved slightly. In 2020, 3-month mortality of NSCLC varied from 3·0% [2·2 - 3·8] for localized to 9·6% [8·1 - 11·0] for locally advanced to 29·2% [27·8 - 30·6] for metastatic and was 24·8% [22·3 - 27·3] for SCLC. Interpretation: To our knowledge KBP cohorts have been the largest, prospective, real-world cohort studies involving LC patients conducted in worldwide. The trend found in our study shows an increase in LC in women and still a large proportion of patients diagnosed at metastatic or disseminated stage. Funding: The study was promoted by the French College of General Hospital Pulmonologists with financial support of industrials laboratories.